2014
DOI: 10.2139/ssrn.2539521
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Institutions, Innovation and Economic Growth: Estimates for European Countries

Abstract: This paper investigates the theoretical and empirical foundations of the links between inclusive institutions, innovation and economic growth. Its first contribution to the literature is to provide a non-scale R&D-based growth model incorporating negative externalities linked to low institutional quality that not only affect the productivity of private and human capital, but also constrain the diffusion of existing technological knowledge. In turn, these negative externalities reduce economic growth. The secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 83 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…Andreea et al [5]analyzed the impact of innovation on the long-term economic growth of the Czech Republic, Hungary and Poland using multiple regression models based on the following independent variables (Number of patents, number of trademarks, research and development expenses, research and development activities, human capital, foreign direct investment) The results found that the number of patents and trademarks, human capital and foreign investment had a positive impact on economic growth, competitiveness and sustainable development. Giorgio and Margherita [17]tried to test the relationship between innovation and economic growth in a number of European countries using a multiple regression model. The study found that technology was the most important tool for increasing a country's economic growth rate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Andreea et al [5]analyzed the impact of innovation on the long-term economic growth of the Czech Republic, Hungary and Poland using multiple regression models based on the following independent variables (Number of patents, number of trademarks, research and development expenses, research and development activities, human capital, foreign direct investment) The results found that the number of patents and trademarks, human capital and foreign investment had a positive impact on economic growth, competitiveness and sustainable development. Giorgio and Margherita [17]tried to test the relationship between innovation and economic growth in a number of European countries using a multiple regression model. The study found that technology was the most important tool for increasing a country's economic growth rate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More recent empirical evidence explains that institutional differences affect the level of R&D spillovers. For instance, d'Agostino and Scarlato [26] show that inclusive institutions have a positive association with innovation. However, the host country's differences from the home country in terms of institutional regulations harm foreign subsidiary performance [27].…”
Section: Plos Onementioning
confidence: 99%
“…As a result, prospective entrepreneurs are discouraged from undertaking innovation investment. d'Agostino and Scarlato (2016) develop an empirical link between government institutions and economic growth through the intermediating role of innovation. The study confirms that inclusive institutions magnify the effects of technology shocks on economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%